Aktualisasi Peran Pegadaian Dalam Pengembangan Usaha Menurut Perspektif Bisnis Syariah (Studi Kasus pada Usaha Pedagang Kaki Lima di Watampone) - Agusandi Pratama (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
This research discusses the actualization of the role of pawnshops in business development according to the Islamic business perspective. This research is conducted to measure how much the role of pawnshops in developing street vendors in Watampone is used by sellers in trading. Looking at the work of the majority of street vendors, the majority of entrants, therefore researchers are interested in discussing the budget costs incurred in developing the business. This study aims to determine the role of pawnshops in developing street vendors in Watampone. Based on the objectives of the above research, the type of research used is field research using a qualitative approach. This study uses the method of observation, interviews, and documentation in collecting the required data. The collected data is then processed using Descriptive Analysis techniques and interactive analysis models. The results of the analysis show that the role of pawnshops has a significant effect in developing a street vendor business in Watampone. The magnitude of the influence of the role of pawnshops on street vendors continues to increase for 10 years. The result can be used as a reference to find out the influence of the role of pawnshops on street vendors in Watampone.